2021
DOI: 10.1186/s12894-021-00905-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of kidney stone disease: a cross-sectional study in the southeast of Iran

Abstract: Background The prevalence of kidney stones in the world is increasing and environmental factors seem to play a major role in this issue. The aim of the present study was to investigate the prevalence of risk factors of kidney stones in the adult population of Rafsanjan city based on the data of the Rafsanjan Cohort Study (RCS). Methods In the baseline phase of this study, 10,000 people aged 35 to 70 years are enrolled in the RCS, as one of the pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 22 publications
7
22
0
1
Order By: Relevance
“…The high prevalence of renal stones in non-diabetic and normotensive people could be due to the relatively young age of the study population as in other studies; diabetes mellitus and hypertension have been recorded as significant risk factors for renal stones as mentioned above. High BMI, which means overweight or obesity, was noted to increase nephrolithiasis incidence in study participants, and a similar observation was also made by some other studies [ 2 , 14 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The high prevalence of renal stones in non-diabetic and normotensive people could be due to the relatively young age of the study population as in other studies; diabetes mellitus and hypertension have been recorded as significant risk factors for renal stones as mentioned above. High BMI, which means overweight or obesity, was noted to increase nephrolithiasis incidence in study participants, and a similar observation was also made by some other studies [ 2 , 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…Renal stones were more prevalent in the non-diabetic group in our study population. However, another study proposed that diabetes mellitus puts its patients at the risk of renal stone formation [ 14 ]. This study presented a high frequency of renal stones among patients with normal blood pressure, in contrast to a study that reported hypertension as a risk factor for renal stone generation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were significant differences in personal habits such as alcohol consumption, water consumption, and diet (seafood or high fat) between the KSD and Control groups. Studies have confirmed a strong correlation between alcohol consumption, high-fat diet, and fish or shellfish intake and KDS prevalence [ 21 , 22 ]. This is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted in the southeast of Iran showed a high risk of kidney stone development for male gender (OR, 1.57; 95% CI, 1.39 to 1.76), higher BMI (25 to 29.9 kg/m 2 OR, 1.24, 95% CI 1.11 to 1.40 and ≥ 30 kg/m 2 OR: 1.30, 95% CI 1.14 to 1.48). 4 Additionally, Taylor et al found an association between obesity and KSD regarding gender, which shows the multivariable relative risk for stone formation in men with a BMI of 30 or greater compared with men with a BMI of 21 to 22.9 was 1.33 (95% CI 1.08-1.63), and the corresponding relative risks for the same categories of BMI in older and younger women were 1.90 (95% CI, 1.61-2.25) and 2.09 (95% CI, 1.77-2.48), respectively. 26 According to data from the nationwide, population based study in Taiwan, the age adjusted prevalence in 2010 in male and female subjects was 9.01% and 5.79%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…2 KSD can contribute to pain, infection, urinary tract obstruction, thus affecting patients' kidney function, quality of life and comorbidities, which have a huge impact on human health. 3,29 There are many factors associated with the development of KSD, including age 4 , male gender 5 , obesity 6 , genetics 7 , environmental pollutants 8 , habits and customs. 9 By avoiding the modi able risks factors may promote human health and reduce medical burden.…”
Section: Introductionmentioning
confidence: 99%